Particle number and current in Dirac field in the closed universe - Dhungel, PR; Khanal, U (Scientific World, 2011)
The behavior of the particle number and particle current of the free Dirac field in the closed FRW universe has been explored. Although the particle number is conserved for the massless fields as expected, it is not for the massive ones. So, there is a finite particle current in any finite sized volume of the universe. Such currents tend to enhance the density contrast over time. It is seen that the momenta of the Dirac particle is quantized in a closed FRW model. The particles distribute themselves in such a way as to resemble that required for the flattened rotation curves of galaxies. Key words: Closed Universe; Dirac field; Comoving particle number density DOI: http://dx.doi.org/10.3126/sw.v9i9.5508 SW 2011; 9(9): 4-7